2008
DOI: 10.1021/jf8003702
|View full text |Cite
|
Sign up to set email alerts
|

Gibberella Ear Rot of Maize (Zea mays) in Nepal: Distribution of the Mycotoxins Nivalenol and Deoxynivalenol in Naturally and Experimentally Infected Maize

Abstract: The fungus Fusarium graminearum (sexual stage Gibberella zeae) causes ear rot of maize (Zea mays) and contamination with the 8-ketotrichothecenes nivalenol (1) or 4-deoxynivalenol (2), depending on diversity of the fungal population for the 4-oxygenase gene (TRI13). To determine the importance of 1 and 2 in maize ear rot, a survey of naturally contaminated maize in Nepal was combined with experiments in the field and in a plant growth room. In the survey, 1 contamination was 4-fold more frequent than 2 contami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 27 publications
(41 reference statements)
1
32
0
Order By: Relevance
“…Trichothecene production need not be correlated with phylogenetic lineage (41). In the populations we sampled, all of the lineage 3 and lineage 7 isolates produced deoxynivalenol, and all lineage 2 isolates and all but one lineage 6 isolate produced nivalenol ( (28), with DON-producing strains being perceived as more virulent than NIVproducing strains (8). Trichothecene production is not thought to be important in aggressiveness toward rice.…”
Section: Discussionmentioning
confidence: 94%
“…Trichothecene production need not be correlated with phylogenetic lineage (41). In the populations we sampled, all of the lineage 3 and lineage 7 isolates produced deoxynivalenol, and all lineage 2 isolates and all but one lineage 6 isolate produced nivalenol ( (28), with DON-producing strains being perceived as more virulent than NIVproducing strains (8). Trichothecene production is not thought to be important in aggressiveness toward rice.…”
Section: Discussionmentioning
confidence: 94%
“…In a recent survey of maize seed samples in Nepal, in contrast, nivalenol contamination was four-fold more frequent than deoxynivalenol contamination, and nivalenol producers (TRI13) of the F. graminearum clade were isolated more than twice as frequently as deoxynivalenol producers (jTRI13) (Desjardins et al 2008). The high frequency of nivalenol contamination is of special concern because nivalenol has proven to be more toxic than deoxynivalenol in most animal systems (Desjardins 2006). In addition, the high frequency of nivalenol producers of the F. graminearum clade suggested that deoxynivalenol-producing F. graminearum sensu stricto, which appears to be dominant on maize elsewhere, might be less common on maize in Nepal.…”
Section: Introductionmentioning
confidence: 95%
“…Fungi of the Fusarium graminearum clade (teleomorphs Gibberella species) infect wheat, barley, maize, and other cereal crops worldwide and contaminate grain with trichothecene mycotoxins that are harmful to human health (Desjardins 2006;Leslie & Summerell 2006). On smallholder farms in the foothills of the Himalayan Mountains of Nepal, the F. graminearum clade causes Gibberella ear rot of maize and contamination with the 8-ketotrichothecenes nivalenol and deoxynivalenol (Desjardins et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations